1996
DOI: 10.1002/etc.5620151008
|View full text |Cite
|
Sign up to set email alerts
|

Structure—activity relationships for chloro‐ and nitrophenol toxicity in the pollen tube growth test

Abstract: Abstract-Acute toxicity of 10 chlorophenols and 10 nitrophenols with identical substitution patterns is analyzed with the pollen tube growth (PTG) test. Concentration values of 50% growth inhibition (IC50) between 0.1 and 300 mg/L indicate that the absolute sensitivity of this alternative biotest is comparable to conventional aquatic test systems. Analysis of quantitative structure-activity relationships using lipophilicity (log K ow ), acidity (pK a ), and quantum chemical parameters to model intrinsic acidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 29 publications
(17 reference statements)
0
30
2
Order By: Relevance
“…values are unrealistic i.e., much too high compared to toxicity data for these compounds in other species Ž . Cronin and Schultz, 1996;Schuurmann et al, 1996 . Iẗc an concluded that for the phenols at least, toxicity is not attributable solely to the non-ionized form, but also Ž .…”
Section: Ph Xmentioning
confidence: 98%
See 2 more Smart Citations
“…values are unrealistic i.e., much too high compared to toxicity data for these compounds in other species Ž . Cronin and Schultz, 1996;Schuurmann et al, 1996 . Iẗc an concluded that for the phenols at least, toxicity is not attributable solely to the non-ionized form, but also Ž .…”
Section: Ph Xmentioning
confidence: 98%
“…Other workers have included a consideration of p K directly in the a QSAR for the prediction of the toxicity of phenols ŽBalaz et al, 1996;Pirselova et al, 1996;Kishino andˇˇ´. Kobayashi, 1996a;1996b;Schuurmann et al, 1996 .Ž . Cronin and Schultz 1996 reported a QSAR for the prediction of the toxicity of 120 phenols with log P and E as significant parameters.…”
Section: Ph Xmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, two aniline compounds and PCP were included which are suggested to have a polar narcotic MoA, as well as ethylenglycol, which has a narcotic MoA. Structure-based MoA assignments generate equivocal results concerning the separation between polar narcosis and uncoupling (Schüürmann et al, 1996), with some studies classifying the anilines and PCP as uncouplers, while other studies classifying them as polar narcotics (Russom et al, 1997;Schüürmann et al, 1997;Argese et al, 2001;Spycher et al, 2008a;Janssens et al, 2011;Dom et al, 2012). Since these test chemicals are not unequivocally classified as uncouplers, the TMRM assay could not be used for the selection of equipotent test concentrations.…”
Section: Moa Specific Gene Expression Profile At Cytotoxic Based Concmentioning
confidence: 99%
“…4,5 It is well-known that the isomers of nitrophenol are serious environmental pollutants due to their potential toxicity (carcinogen, teratogenic and mutagenic) to human beings, animals, and plants even at a very low concentration. [6][7][8] The harmful effects of NP on humans include headache, fever, breathing trouble, and even death at high levels of exposure. 9 In addition, the NPs are readily accumulated in organisms and are hard to naturally degrade because of the high structure stability.…”
Section: Introductionmentioning
confidence: 99%